Perampingan Struktur Birokrasi di Indonesia: Urgensi dan Konsekuensi - Dahlia Dahlia (Jurnal Transformasi Administrasi, 2020)
Under second term of President Joko Widodo’s administration, Indonesia is about to adopt vivid reform discourse, i.e. to flatten bureaucratic structure through streamlining the echelon system as a response to the change and development. Notwithstanding, it is inevitable that this reform would be of no overarching consequences. This paper attempts to seek the genuine urgencies and consequences of flattening the bureaucratic structure through streamlining the echelon system. Relevant literature following the criteria of systematic review method was extracted and independently reviewed. It is derived that it was the factor of corruption, competitiveness and human resource that urged the bureaucratic structure to flatten. Further, a change in working culture and environment as well as career management of the state apparatus appeared to be the consequences of such reform.